Interactions of Copper (II) Chloride with ß-Cyclodextrin in Aqueous Solutions - Ribeiro, A. C. F. (2006)
The interaction between copper (II) chloride and the carbohydrate ß-cyclodextrin (ß-CD) has been studied in aqueous solutions (298.15 K and 310.15 K) using measurements of diffusion coefficients and electrical conductivity. Significant effects on the electrical conductivity were observed in the presence of the ß-CD, suggesting interactions between this carbohydrate and copper chloride. Support for this came from diffusion coefficient measurements. These studies have been complemented by molecular mechanics calculations.